Process improvements and techno-economic analyses for the production of short-chain fructose-containing oligosaccharides from sucrose and Jerusalem artichoke tubers - Bedzo, Oscar Koku Kplorm (Stellenbosch : Stellenbosch University., 2020)
Thesis (PhD)--Stellenbosch University, 2020.